Analysis of the demand for the alternative currency WIR. (3rd October 2019) - Gawthorpe, Katerina
This case study outlines an empirical analysis of factors explaining the substantial demand for the oldest and the largest private currency, Switzerland's Wirtschaftsring (WIR). The method of analysis consists of vector autoregressive (VAR) models accompanied by a vector error correction model (VECM). First, the empirical analysis proves that WIR circulates as a substitute to the Swiss Franc. This result warrants the construction of a subsequent model to reveal the characteristics responsible for the switch. The variables of interest consist of the inflation rate and the interest rate for the Swiss Franc and the Swiss gross domestic product (GDP). The outcome supports an elevation of demand for the WIR currency in times connected with higher inflation for the Swiss Franc and more expansive credit denominated in the national currency. Finally, the WIR demand appears to behave countercyclical in respect to the Swiss GDP.